In Vitro Assessment of Penicillium expansum Sensitivity to Difenoconazole - Mohammed Khadiri; Hassan Boubaker; Abdelaaziz Farhaoui; Said Ezrari; Mohammed Radi; Rachid Ezzouggari; Fouad Mokrini; Essaid Ait Barka; Rachid Lahlali (Microorganisms)
Penicillium expansum causes blue mold, a major post-harvest disease affecting apples. This disease is commonly managed using fungicides, including Difenoconazole (Dif), a demethylation inhibitor (DMI) approved for its control. This investigation aims to evaluate the baseline sensitivity of 100 P. expansum isolates to Difenoconazole. The isolates were collected from symptomatic apples in 34 storage warehouses across the Fes-Meknes and Draa-Tafilalet regions over three years (2020, 2021, and 2022). The study revealed an increase in the percentage of inhibition of mycelial growth and spore germination of P. expansum proportional to the increasing concentration of the fungicide. Moreover, the results indicate that 46 isolates were able to develop even at a concentration of 5 µg/mL of Dif (the suggested discriminatory dose), indicating reduced sensitivity to this fungicide. The analysis of the values of the effective concentration to inhibit 50% (EC50) of mycelial growth of P. expansum ranging from 0.027 to 1.673 µg/mL (mean: 0.263 µg/mL, variation factor: 62.507) and for spore germination from 0.0002 to 0.787 µg/mL (mean: 0.048 µg/mL, variation factor: 4113.835). The wide variation in EC50 values indicates significant variability in the isolates’ responses to Dif, likely due to diverse sampling in space and time. Our results showed that some P. expansum isolates could grow even at high concentrations of Dif, indicating limited efficacy of this treatment. The EC50 of five isolates exceeded 0.92 µg/mL, suggesting potential resistance. This study indicates reduced sensitivity and possible emergence of resistant strains. Notably, it is the first evaluation of P. expansum sensitivity to Dif in Morocco.